Global economics crisis and nutrition security in Africa - Babu, Suresh Chandra (African Journal of Food, Agriculture, Nutrition and Development, 2009)
For nearly a decade, sound economic policies and greater external support, in the forms of debt relief and increased investment and inflows contributed to robust economic growth in many African countries. During 2007 and 2008, though, food and fuel price shocks put inordinate strains on these nations’ balance sheets, growth prospects and potential to reduce poverty. These strains have since been compounded by the global economic crisis, which now threatens to reverse the region’s more recent movement toward meeting the Millennium Development Goals [1].The global recession has effectively reduced export demand, commodity prices and foreign investment and inflows, generating negative effects on terms of trade and household incomes. These negative effects exacerbate living and working conditions in Africa that were already worsened by the food crisis. African farmers in particular have had little resources with which to respond to these crises. Poor infrastructure, poor quality seeds and soil, limited technology and investment in research and development and a lack of access to capital, among other obstacles, leave African farmers with a diminished capacity to respond to the current crisis [2]. African nations, made more vulnerable by the food and fuel crisis, now face a worsened outlook given the deeper vulnerability imposed upon them by the economic crisis’ adverse and potentially prolonged effects. This potentially dire outlook begs the question, what kinds of policies and programs are needed to protect the vulnerable? Though the experience is scanty on how to implement large scale interventions, lessons learned from other parts of the world and from past crisis might provide the first steps forward toward devising a solution.